2017
DOI: 10.1016/j.wasman.2017.06.051
|View full text |Cite
|
Sign up to set email alerts
|

Enablers towards establishing and growing South Africa’s waste to electricity industry

Abstract: In South Africa the electricity generation mix is relatively un-diverse whereas globally the transformation of the sector is advancing rapidly. Coal remains the predominant fuel source and limited success has to date been achieved in the renewable energy sector. The electricity generation sector is therefore hindered from moving towards an electricity generation landscape where alternative fuel sources is utilised. This research is aimed at gaining insight into the enablers that led towards an increasing trend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Similar studies in selected African countries concur that, while the mean overall LHV for MSW can be as low as 5.0-6.0 MJ kg −1 , those for the urban centers have higher calorific values, for example Addis Ababa, Ethiopia (12.0 MJ kg −1 ), South Africa (7.0 MJ kg −1 ) and Nigeria’s southern and northern cities (13.1 and 11.9 MJ kg −1 , respectively) (Amsterdam and Thopil, 2017; Cambridge Industries Energy, 2017; Ogunjuyigbe et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar studies in selected African countries concur that, while the mean overall LHV for MSW can be as low as 5.0-6.0 MJ kg −1 , those for the urban centers have higher calorific values, for example Addis Ababa, Ethiopia (12.0 MJ kg −1 ), South Africa (7.0 MJ kg −1 ) and Nigeria’s southern and northern cities (13.1 and 11.9 MJ kg −1 , respectively) (Amsterdam and Thopil, 2017; Cambridge Industries Energy, 2017; Ogunjuyigbe et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…While the US, the EU and selected Asian countries have demonstrated success in this regard, waste-to-energy (WtE) technologies are yet to be fully embraced in most African cities (Scarlat et al, 2015). So far, only a few have recorded successes in co-generation (Namibia, Nigeria, South Africa), and landfill gas (LFG) to electricity (Mauritius, South Africa) (Amsterdam and Thopil, 2017; Ogunjuyigbe et al, 2017). Some, like Cameroon, have only managed to recover and flare bio-methane from MSW landfills mostly for safety and environmental reasons (Roopnarain and Adeleke, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This increment is attributed to urbanisation, population growth and economic development. Similarly, to [10] reported that South Africa produces a total of 108 million tons of MSW per year, with 59 million tons being general waste and 1 million ton representing hazardous waste, while the remainder is unclassified. From 59 million tons of general MSW, 10% is recyclable, of which 53.1 million tons are sent to landfill.…”
Section: Introductionmentioning
confidence: 99%
“…So far, only a few have recorded successes. Undoubtedly, the investment and technical demands for advanced waste treatment systems are the major reasons for the slow adoption of WtE in emerging countries [2]. Additionally, recent data on characteristics of the MSW is missing in most developing countries.…”
Section: Introductionmentioning
confidence: 99%